1997
DOI: 10.1162/jocn.1997.9.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Eye Movements During Visual Imagery Reflect the Content of the Visual Scene

Abstract: In nine naïve subjects eye movements were recorded while subjects viewed and visualized four irregularly-checkered diagrams. Scanpaths, defined as repetitive sequences of fixations and saccades were found during visual imagery and viewing. Positions of fixations were distributed according to the spatial arrangement of subfeatures in the diagrams. For a particular imagined diagrammatic picture, eye movements were closely correlated with the eye movements recorded while viewing the same picture. Thus eye movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
325
4
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(367 citation statements)
references
References 44 publications
34
325
4
4
Order By: Relevance
“…Brandt and Stark (1997) recently found that the pattern of eye movements was similar when viewers looked at checkered diagrams and when they formed images of them from memory. However, fixations tended to be 75-100 ms longer during imagery than actual looking.…”
Section: Illusions and Imagerymentioning
confidence: 99%
“…Brandt and Stark (1997) recently found that the pattern of eye movements was similar when viewers looked at checkered diagrams and when they formed images of them from memory. However, fixations tended to be 75-100 ms longer during imagery than actual looking.…”
Section: Illusions and Imagerymentioning
confidence: 99%
“…Brandt and Stark (1997) showed that spontaneous eye movements occurred during visual imagery and that these eye movements closely reflected the content and spatial relations from the original picture or scene. The participants were first introduced to a simple visual grid pattern that they were to memorize; shortly afterward, they were asked to imagine the pattern.…”
Section: Experiments 2: Viewing and Then Describing A Picturementioning
confidence: 99%
“…Instead, all of our mental representations are propositional (Pylyshyn, 2002(Pylyshyn, , 2003. Spivey and Geng (2001) and Spivey et al (2000) had a different approach than Brandt and Stark (1997) and Laeng and Teodorescu (2002). They interpreted their results in an "embodied" view of the mind (e.g., Ballard, Hayhoe, Pook, & Rao, 1997;Spivey, Richardson, & Fitneva, 2004) whereby motor processes, such as eye movements, are naturally and tightly coupled with the perceptual and cognitive processes that subserve mental representations.…”
Section: Introductionmentioning
confidence: 99%
“…De plus, les séquences oculomotrices ont sans doute un rôle dans la mémoire et la formation des images mentales. Ainsi, S.A. Brandt et al [19] L'imagerie fonctionnelle a permis d'explorer l'activité corticale mise en jeu lorsqu'on demande à des sujets de reproduire de mémoire une séquence qu'ils viennent d'effectuer de façon visuellement guidée [20][21][22][23]. En plus du réseau cortical impliqué dans le contrôle des saccades simples, les séquences de saccades activent un circuit composé principalement du précuneus, d'une région située dans le sillon intrapariétal, d'une région antérieure au COS et d'une région antérieure au COF, située dans le sillon frontal supérieur, qui correspond à un foyer déjà impliqué dans la mémoire spatiale à court terme (voir plus haut) [14] ou dans l'exploration spatiale [15].…”
Section: Contrôle Cortical Des Séquences De Saccadesunclassified